Pengaruh Program “Social Enterpreneurship” Kelompok ODHA Terhadap Stigma Masyarakat Tentang HIV/AIDS Di Daerah Binaan KPA Kota Kediri. - Siti Asiyah; Susanti Pratamaningtyas; Suwoyo Suwoyo (coba, 2015)
Sixth goal in the MDGs are handle a variety of the most dangerous infectious diseases. At the top is intended to handle HIV, the virus that causes AIDS. The disease is a devastating impact not only on public health but also to the overall state. This study aims to look at the effect of social entrepreneurship program for public stigma about HIV / AIDS. Analytical research design using cross sectional correlational techniques. The study population is the ODHA, which had already independently of 50 people. Samples were taken by simple random sampling technique, a number of 44 people. Statistical analysis was entrepreneurship programs that are run by people living with HIV have not succeeded run and people living with HIV is almost entirely feel the stigma which is given by the society. Chi Square Results obtained Alpha 0:00 less than Alpha 0.05. This means that, the Social Entrepreneurship Program affect the public stigma about HIV / AIDS. The results of the study can be used to support the Government's program to empower of ODHA. Keywords: Social entrepreneurship, Stigma, ODHA